(untitled) (Argumentum, 2012)
The above quote, by a prestigious and often-cited capitalist economic analyst, brutally describes a constant underlying process of capitalism in general – not just in the U.S. but capitalism as an economic system. This is a process which has been in existence since the system began 500 years ago. The prominent bourgeois economic consultant to Wall Street, also a former Lehman Bank executive, is well known for his sharp characterizations of the economic crisis. He is the originator of the phrase “the mother of all jobless recoveries,” referring to the 2009-2010 so-called “recovery.”